Diagnostic accuracy of barium enema versus full‐thickness rectal biopsy in children with clinically suspected Hirschsprung's disease: A comparative cross‐sectional study - Tesfahunegn Hailemariam; Abenezer Kebede Bekele; Tsegahun Manyazewal; Daniel Zewdneh Solomon; Yocabel Gorfu; Zelalem Shiwarega; Tewodros Getinet; Meti Wole; Samrawit Solomon; Samuel Sisay Hailu (Health Science Reports, 2024)
Abstract Background and Aims Hirschsprung's disease (HSD) remains a common cause of pediatric intestinal obstruction. Barium contrast enema (BE) is the primary imaging modality for the evaluation of clinically suspected cases. Here, we aimed to assess the diagnostic accuracy of BE in children with clinically suspected HSD when compared to a gold standard full‐thickness rectal biopsy (FTRB). Methods We recruited and consecutively enrolled children with clinically suspected HSD at two tertiary teaching hospitals. Participants underwent BE imaging and two radiologists interpreted the findings independently. Participants further underwent FTRB by pediatric surgeons as the confirmatory test. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operating characteristics (ROC) with the area under the curve (AUC) were calculated on Stata version 14.2, taking FTRB as the standard. Results We enrolled 55 cases, of which 49 completed the evaluation and were included in the final analysis. The median age was 9.4 months (interquartile range: 2–24], with a male‐to‐female ratio of 4.4:1. The sensitivity, specificity, PPV, and NPV of BE were 0.95 (95% confidence interval [CI] [0.81–0.99]), 0.73 (95% CI [0.39–0.94]), 0.92 (95% CI [0.82–0.97]), and 0.80 (95% CI [0.50–0.94]), respectively. On AUC, the diagnostic accuracy of BE compared to the confirmatory FTRB was 0.84 (95% CI [0.69–0.98]). The diagnostic accuracy was higher in neonates (ROC: 1.00) when compared to infants (ROC: 0.83) or those above 1 year of age (ROC: 0.798). HSD‐suggestive BE findings were associated with absence of ganglion cells on FTRB (χ2 = 23.301, p < 0.001). Inverted rectosigmoid ratio and transition zone were more sensitive in detecting HSD of 0.92 (95% CI [0.74–0.98]) and 0.81 (95% CI [0.63–0.92]), respectively. Conclusion BE is sufficiently accurate in the diagnosis of children with HSD, suggesting BE would likely be used to inform surgical management in settings where confirmatory biopsy is lacking. However, clinical judgment is warranted in interpreting negative BE findings.